Nutritional modelling for pigs and poultry - Sakomura, N. K.; Gous, R.; Kyriazakis, I.,; Hauschild, L. (CABI, 2015)
Modelling is a useful tool for decision making in complex agro-industrial scenarios. The book contains a selection of the papers presented at the International Symposium of Modelling in Pig and Poultry Production 2013, and brings together the best and most recent academic work on modelling in the pig and poultry industries, with a particular emphasis on nutrition. It reviews basic modelling concepts, descriptions and applications of production models and new methods and approaches in modelling. The book is suitable for researchers and students of animal nutrition and veterinary scientists.